Penyuluhan dan pelatihan Resusitasi Jantung Paru (RJP) pada Siswi MTsS Al-Falah Kota Padang - Irwadi, Irwadi; Elfira, Yenni; Rahmaddian, Tosi (Penamas: Journal of Community Service, 2024)
Emergency incidents can occur anywhere, at any time, and to anyone, including at school. Cardiac arrest is an emergency that can threaten human life. Cardiac arrest conditions must immediately receive first aid as soon as possible to prevent death. Help is provided by providing cardiopulmonary resuscitation (CPR) and helpers who have the ability and knowledge to provide action. The phenomenon of public knowledge about handling emergencies is minimal, including the female students of MTS Al-Falah. Based on this, it is necessary to provide outreach activities and CPR training regarding initial emergency management in the school environment. So that female students have basic knowledge and can carry out initial treatment for cardiac arrest and respiratory arrest before being taken to hospital. To help and as a reminder, a guide module is provided for carrying out CPR. MTsS Al-Falah, Padang City, is in the working area of the Ikur Koto Community Health Center, which is 4 km from the Community Health Center. Currently, the implementation and evaluation have been carried out since June 2023. The assessment results showed an increase in students' knowledge and skills in carrying out CPR.